Find the product of (-3xyz) (-4/9x^2z) (-27/2xy^2z) and verify the result for x=2,y=3,z=-1. Please explain step by step and verif

Question

Find the product of (-3xyz) (-4/9x^2z) (-27/2xy^2z) and verify the result for x=2,y=3,z=-1.

Please explain step by step and verify with the process of L.H.S. or R.H.S.​

in progress 0
Allison 4 weeks 2021-08-15T10:10:22+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-08-15T10:11:37+00:00

    Answer:

    Here’s Your Answer

    Step-by-step explanation:

    We have,−3xyz(49x2z)(−272xy2z)=(−43x3yz)(−272xy2z)=18x4y3z2

    Now, for x=2, y=3 and z=−118(2) 4(3) 3 (−1)2=18×16×27×1 = 7776

    Hope It Helps

    If It Did Please Mark It As The Brainliest Answer.

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )